Attitudes of Physicians and Nurses in Oman Toward Mandatory COVID-19 Vaccination - Abdallah M. Badahdah; Nawal Al Mahyijari; Ryan Badahdah; Furqan Al Lawati; Faryal Khamis (Oman Medical Journal, 2022)
Objectives: To investigate the relationship between attitudes toward COVID-19 vaccines and disapproval of the policy of mandatory COVID-19 vaccination among unvaccinated physicians and nurses in Oman. Methods: The subjects were (N = 346) unvaccinated physicians and nurses in Oman. Their demographic data and attitudes regarding COVID-19 vaccines and mandatory vaccination policy were collected through an anonymous web-based survey and statistically analyzed. Results: The participants’ negative attitudes toward COVID-19 vaccines were positively related (r = 0.68, p < 0.001) to the extent of their non-support for COVID-19 mandatory vaccination policy. Analysis of variance test showed that after controlling for age, male healthcare providers were more likely to endorse mandating COVID-19 vaccinations. There was no difference between physicians and nurses in support of mandatory vaccination, after controlling for age. Conclusions: Regardless of job type, male, and older physicians, and nurses in Oman were more supportive of mandatory COVID-19 vaccination than their younger and female counterparts. This research provides insights from an Arabian Gulf country about the attitudes of its unvaccinated healthcare providers toward compulsory COVID-19 vaccination.